Pengaruh Akuntansi Lingkungan dan Green Intellectual Capital terhadap Nilai Perusahaan dengan Sustainability Report Independent Assurance sebagai Variabel Moderasi - Kusumaningrum, Meyrina; Astuti, Christina Dwi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to obtain empirical evidence about the influence of environmental costs, environmental accounting information disclosures, Green Human Capital, Green Structural Capital, and Green Relational Capital on firm value with sustainability report independent assurance as a moderating variable. The analytical method used in this research is panel data moderated regression analysis method with purposive sampling technique. The number of observations in this research was 204 basic materials sector companies listed on the IDX in the period 2021 to 2023. The results of this research show that Green Structural Capital dan Green Relational Capital variables have a positive effect on firm value, while the environmental costs, environmental accounting information disclosures, and Green Human Capital variables have no effect on firm value. Meanwhile, the sustainability report independent assurance is not able to strengthen the influence of the environmental costs, environmental accounting information disclosures, Green Human Capital, Green Structural Capital, and Green Relational Capital on firm value.